Preparation of astaxanthin/zeaxanthin-loaded nanostructured lipid carriers for enhanced bioavailability: Characterization-, stability-and permeability study - Radić Kristina; Barbosa Ana Isabel; Reis Salette; Marijan Marijan; Lima Sofia Antunes Costa; Čepo Dubravka Vitali (Acta Pharmaceutica)
Astaxanthin (ASTA) and zeaxanthin (ZEA) are xanthophyll carotenoids showing a wide spectrum of health-promoting properties. However, their utilization is limited, mostly due to poor water solubility, limited bioavailability, and a tendency to oxidate, as well as photo- and thermal instability. The aim of this work was to develop ASTA- and ZEA-loaded nano-structured lipid carriers (NLCs) that would protect them against degradation and improve their intestinal stability/permeability. Obtained NLCs were characterized by an effective diameter of 294 nm for ASTA-NLC and 280 nm for ZEA-NLC; polydispersity index (PDI) lower than 0.2; and zeta potential of –29.4 mV and –29.0 mV, respectively. Interestingly, despite similar physicochemical characteristics, our investigation revealed differences in the encapsulation efficiency of ASTA-NLC and ZEA-NLC (58.0 % vs. 75.5 %, respectively). Obtained NLCs were stable during a 21 day-storage period in the dark at room temperature or at 4 °C. Investigation of gastrointestinal stability showed no change in effective diameter and PDI under gastric conditions while both parameters significantly changed under intestinal conditions. Our results showed for the first time that both ASTA- and ZEA-NLCs intestinal absorption investigated in the in vitro model is significantly increased (in relation to pure compounds) and is affected by the presence of mucus. This study provides useful data about the advantages of using NLC as a delivery system for ASTA and ZEA that might facilitate their applications in the food and pharmaceutical industry.